Far from the madding crowd - Hardy, Thomas, 1840-1928.; Morgan, Rosemarie; Russell, Shannon (New York, N.Y., USA : Penguin Books., 2000)
Bathsheba Everdene is courted by three young men: an adventurer, a young farmer who becomes bailiff of the farm she inherits, and a neighboring farmer.
Includes bibliographical references (p. 354-391).
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Young Adult
Keywords: Farm life -- Fiction; Man-woman relationships -- Fiction; Farm life -- Fiction; Man-woman relationship -- Fiction; Great Britain -- Fiction; Great Britain -- Fiction